Community Crime Prevention Research Trends: A Bibliometric Analysis - Fahmi, Teuku; Sulhin, Iqrak; Harahap, Anggi Aulina (Technium Social Sciences Journal, 2025)
Research into community crime prevention has become a major area of concern in recent decades. However, a comprehensive and systematic literature review on this topic is still relatively scarce. This study analyzes research trends on community crime prevention using bibliometric analysis and VOSviewer visualization. The scope of this study included 84 articles published in 62 source titles indexed by Scopus from 1981 to December 2024. The results of the bibliometric analysis show that research trends on community crime prevention vary in terms of the development of scientific article themes, reviews of the diversity of crime prevention strategies, and collaboration between researchers. In addition, the results of the analysis also identified an increase in interest in topics that emphasize community-based approaches to crime prevention.